2017
DOI: 10.1111/edt.12355
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of the relationship between facial injury and mild traumatic brain injury

Abstract: Mild traumatic brain injury should be suspected in patients with facial injuries and particularly those with lower face lacerations, midface fractures, moderate to severe facial injury and presence of multiple injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Similar results were found in other studies, in which individuals presented with traumatic brain injuries associated with facial trauma resulting from motorcycle accidents, ranging from 34.4% to 40%‐45% of cases. Abdul Razak et al verified that the majority of the patients with mild traumatic brain injuries were aged between 18 and 25 years. Conversely, a recent study also investigated oral and maxillofacial trauma in motorcyclists in an Iranian subpopulation, with 85.75% of patients aged 21‐30 years.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in other studies, in which individuals presented with traumatic brain injuries associated with facial trauma resulting from motorcycle accidents, ranging from 34.4% to 40%‐45% of cases. Abdul Razak et al verified that the majority of the patients with mild traumatic brain injuries were aged between 18 and 25 years. Conversely, a recent study also investigated oral and maxillofacial trauma in motorcyclists in an Iranian subpopulation, with 85.75% of patients aged 21‐30 years.…”
Section: Discussionmentioning
confidence: 99%
“…TBI is a leading cause of death and disability among patients with craniofacial fractures. 14-16 This pattern is found within FAIs, especially among self-inflicted injuries. One study found that from 2008 to 2017 firearm-related suicides accounted for 48% of the increase in absolute incidence of TBI-related death.…”
Section: Introductionmentioning
confidence: 79%
“…Razak et al reported the presence of mild traumatic brain injury in patients with facial lacerations to be as high as 41.4%. 7…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%